Assessment Of The Quality Of Signal Transmission In Fiber-Optic Communication Systems With Wave Division Of Channels - et. al., Rixsi Isaxodjaevich Isayev, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
High power a group DWDM signal will lead to a change in the refractive index of OF (optical fiber), as a result of which additional combination products are formed. And also the non-fulfillment of the conditions of a single-mode OF regime in practice leads to the appearance of combination products and the manifestation of non-linearity of the OF. These nonlinear products exert mutual influence between parallel optical channels, which degrades the quality of the optical channels. To justify the influence of the power of a group signal on the power of nonlinear interference and on the quality of communication, the power of four-wave mixing, amplified spontaneous emission, and the Q-factor were calculated. To meet the requirements for the quality of signal transmission through optical communication channels with WDM, optimization of the level of transmitted optical power through the communication channels of systems with WDM and justification of optical amplifiers, alignment of the gain of the optical amplifier, rational selection of the number of optical channels and stabilization of their level by power are proposed. Choosing the optimal level of group signal power and assessing the quality of transmission of optical channels in WDM allows us to solve the problem of scientifically sound design, implementation and effective operation of promising optical communication systems with wave division of channels. The article presents the results of research and analysis of factors affecting the quality of fiber-optic communication systems with wave separation of channels.